2017
DOI: 10.1177/1077546317743121
|View full text |Cite
|
Sign up to set email alerts
|

Active torque control for gear dynamic load suppression in a drum shearer cutting transmission system under impact loads

Abstract: In order to suppress the impact of a loads-induced gear dynamic load of a drum shearer cutting transmission system, an active torque compensation control method is proposed in this paper based on the active disturbance rejection and adaptive neuro-fuzzy control technologies. Using the speed difference between the motor rotor and the first stage gear as a feedback state variable, an active disturbance rejection torque compensation controller is firstly designed for suppressing the dynamic load of the electromec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Zhang et al [8] used Matlab software to conduct a reliable and robust optimization design of the shearer ranging arm transmission system, proving that this design is feasible, practical, and effective. Ge et al [9] proposed active torque control for gear dynamic load suppression in a drum shearer transmission system. Chen et al [10] studied the change in tooth backlash caused by the tooth bulk temperature, which in turn affects the dynamic performance of gear meshing in the shearer.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [8] used Matlab software to conduct a reliable and robust optimization design of the shearer ranging arm transmission system, proving that this design is feasible, practical, and effective. Ge et al [9] proposed active torque control for gear dynamic load suppression in a drum shearer transmission system. Chen et al [10] studied the change in tooth backlash caused by the tooth bulk temperature, which in turn affects the dynamic performance of gear meshing in the shearer.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al studied the electromechanical coupling torsional vibration characteristics of the gear transmission system driven by a low-speed and high-torque permanent magnet synchronous motor, and found that the electromagnetic effect reduces the first natural frequency of the system and inhibits the vibration of the gear [7][8][9]. Ge et al proposed a fuzzy control method based on active disturbance rejection and self-adaptation to suppress effectively the dynamic load of the transmission system [10]. Wang et al analyzed the influence of damping ratio, mesh stiffness and excitation frequency of a planetary gear transmission system, and applied the research results as an analysis basis for the design of transmission system [11].…”
Section: Introductionmentioning
confidence: 99%
“…At present, scholars have done some research work on the whole system of coal shearer and its key components. In the study of the transmission system of the cutting section, the dynamic characteristics of the ranging arm transmission system under the influence of factors such as ranging arm shell deformation and gear meshing temperature have been analyzed mainly by analytical method and analytical-finite element method 3 6 . By means of the obtained dynamics of the conventional system of the ranging arm in particular, Jiang et al 7 further designed a control method for suppressing large amplitude and unstable vibrations of the drive train based on the Routh-Hurwitz stability criterion; Chen et al 8 for the chaotic motion generated by the system and proposed to excite the unsteady motion of the control system by applying periodic resonance; Qin et al 9 optimized the topology of the ranging arm housing and analyzed the effect of the optimized deformed housing on the dynamic characteristics of the drive train; Zeng et al 10 analyzed and studied the dynamics of the coupling between the cutting force of the drum and the height-adjusting hydraulic system using a joint simulation technique; In the study of the haulage unit drive system, Zhang et al 11 proposed a drum load model for slant-cutting conditions, and the dynamics model of the haulage unit drive system is solved and analyzed; Zhou et al 12 used the saddle point approximation method to assess the maximum contact stress of the drive train and analyzed the reliability of the planetary gear system of coal shearer; Dejian et al 13 analyzed the drive characteristics and the dynamics of the haulage unit of a coal shearer with different operating parameters under the influence of longitudinal sway; Zhou et al 14 proposed a method for assessing the reliability of haulage unit drive systems and reliability-based sensitivity analysis and analyzed the planetary gear mechanism in the drive train; for the dynamics analysis of the whole system, Hongyue et al 15 used virtual technology to simulate and analyze the support characteristics of the four slide shoes of the coal shearer under different working conditions; Zhang et al 16 used Workbench finite element simulation software to analyze the modal and pre-stress constrained model of a three-drum coal shearer; Xinwei et al 17 used a combination of numerical solution and experimental verification to analyze the dynamics of the coupled traction-swing of a coal shearer under multiple factors and operating conditions.…”
Section: Introductionmentioning
confidence: 99%